INTELLECTUAL CAPITAL DAN MARKET VALUE: STUDI PERUSAHAAN HIGH-IC INTENSIVE DI BURSA EFEK INDONESIA - Zaki Fakhroni; Irwansyah Irwansyah (Jurnal Riset Akuntansi dan Keuangan, 2017)
Abstract. This research aims to examine the effect of intellectual capital on firms’ market value. Using Pulic’s VAICTM, this study examines the effect of intellectual capital, VACA, VAHU and STVA both partially and aggregately to firms’ market value using market to book value (MBV) as proxy. Population in this study are companies listed on the indonesia Stock Exchange from two different subsectors advertising, printing and property and real estate in the period of observation in 2007-2016. The number of sample is 254 units of observation. Sampling techique using methods of probability/random sampling. The results show that aggregately, intellectual capital (VAICTM) has a positive and significant effect on firms MBV. VACA, VAHU and STVA component proven to have a positive and significant effect towards MBV. Thus, indicates that most investors in Indonesia prefer firms physical assets efficiency to firms efforts in developing intangible assets.